Pembesaran Udang Vaname (Litopenaeus vannamei) Hingga DOC 58 Pada Tambak Tanah dan Semi Beton di Kabupaten Lampung Timur, Lampung - Aprilia, Tulas; Effendi, Irzal Effendi; Aprianta, I Ketut Bimbo; Febriani, Dian (Universitas Madako Tolitoli, 2025)
White shrimp (Litopenaeus vannamei) is one of the leading export commodities of aquaculture in Indonesia. The success of the White shrimp cultivation system is largely determined by proper planning, especially in terms of the suitability of technical aspects of the construction side. Therefore, an analysis of the technical aspects (construction) of earthen and semi-concrete ponds is needed to determine the growth performance and survival of the cultivated White shrimp. This study aims to evaluate the maintenance of White shrimp up to DOC 58 in earthen and semi-concrete ponds in East Lampung Regency. The study was conducted from July to September 2022 at Tambak Suparman Farm located in Sriminosari Village, Labuhan Maringgai District, East Lampung. The method used in this study is descriptive exploratory through the collection of primary and secondary data. The parameters observed include Mean Body Weight (MBW), Average Daily Growth (ADG), feed conversion ratio (RKP) and survival rate (TKH). The data obtained were then analyzed descriptively in the form of tables. The results of the study showed that the maintenance of vaname shrimp in soil and semi-concrete ponds for 58 days showed MBW values ​​of 9.76 g and 8.01 g; ADG of 0.14 g/day and 0.11 g/day; SR of 64.3% and 77.9%; FCR of 1.65 and 1.49; EP during the maintenance obtained was 60% and 66.89%.